Eliminating Government Vehicle Assets in Support of The Green Economy: a Study of International Policy and Practice - Rachman Sucipto; Azaria Eda Pradana; Aska Winarta Putra; Galang Graha Perkasa (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2026)
Government vehicle disposal in Indonesia is primarily conducted through auction mechanisms aimed at optimizing non-tax state revenue (PNBP), ensuring transparency, and improving administrative efficiency. However, from a green economy perspective, this approach may unintentionally prolong the operational life of aging vehicles with high carbon emissions, thereby contributing to environmental degradation and undermining national sustainability goals. This study aims to analyze the implications of government vehicle disposal policies on green economy objectives, compare Indonesia’s practices with those implemented in the United States, Germany, and Japan, and formulate policy recommendations for a more sustainable disposal system. The research employs a descriptive qualitative method using literature review, policy analysis, and comparative analysis of regulations and disposal practices across selected countries. The findings indicate that Indonesia’s disposal policy remains largely focused on fiscal and administrative considerations, whereas developed countries have integrated circular economy principles through vehicle recycling, environmental impact assessments, emission monitoring, and low-emission disposal systems. The study recommends a hybrid disposal model that combines auctions for environmentally compliant vehicles with mandatory recycling for high-emission vehicles, alongside the integration of environmental criteria into disposal regulations and the allocation of auction revenues to support clean energy transition programs. Such measures are expected to balance fiscal objectives with environmental sustainability and climate commitments.